1992
DOI: 10.1071/ea9920473
|View full text |Cite
|
Sign up to set email alerts
|

Fallow management, soil water, plant-available soil nitrogen and grain sorghum production in south west Queensland

Abstract: The effects of tillage frequency (conventional, reduced and zero), primary tillage implement (disc, blade and chisel plough), stubble management (retention and removal), gypsum application, and paraplowing were examined with respect to soil water storage, soil nitrate accumulation, crop establishment, crop growth, grain yield and grain nitrogen content for 4 successive sorghum crops on a sodic, texture-contrast soil in south west Queensland. Retention of sorghum stubble (v. removal) produced an increase in mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Even though the fallow plots had no addition of N, greater N accumulation occurred in maize grown in a fallow–maize system than in a soybean–maize or maize–maize system. Soil water availability as a result of water storage during the fallow period has been attributed to better performance of crops on fallow (Gibson et al, 1992; Schillinger and Bolton, 1993). But greater N uptake and higher chlorophyll in our study indicated that more N was available.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the fallow plots had no addition of N, greater N accumulation occurred in maize grown in a fallow–maize system than in a soybean–maize or maize–maize system. Soil water availability as a result of water storage during the fallow period has been attributed to better performance of crops on fallow (Gibson et al, 1992; Schillinger and Bolton, 1993). But greater N uptake and higher chlorophyll in our study indicated that more N was available.…”
Section: Resultsmentioning
confidence: 99%
“…In Australia, Gibson et al (1992) found that retaining sorghum stubble on the soil increased the sorghum yield by 393 kg ha −1 due to increased WUE because of a greater amount of water stored in and extracted from the soil profile compared with conventional tillage. They also found that decreasing tillage frequency increased soil water extraction; however, no tillage did not result in the optimum yield or WUE.…”
Section: Soil Surface Modificationsmentioning
confidence: 99%
“…An opposite result was found in Australia, where Gibson et al (1992) observed that keeping sorghum stubble on the soil surface increased sorghum yield by 393 kg ha −1 because of increased WUE from the greater amount of water stored in and available to be used by the crop when extracted from the soil profi le compared to conventional tillage. In this study, they found that decreasing tillage frequency increased soil water extraction, but no-tillage did not result in the optimum yield or WUE (Gibson et al, 1992).…”
Section: Crop Growth and Yieldsmentioning
confidence: 90%
“…An opposite result was found in Australia, where Gibson et al (1992) observed that keeping sorghum stubble on the soil surface increased sorghum yield by 393 kg ha −1 because of increased WUE from the greater amount of water stored in and available to be used by the crop when extracted from the soil profi le compared to conventional tillage. In this study, they found that decreasing tillage frequency increased soil water extraction, but no-tillage did not result in the optimum yield or WUE (Gibson et al, 1992). Water use effi ciency can be enhanced by additional availability of soil water, and in the southern High Plains, the addition of soil water through irrigation increased WUE for wheat to 8 kg ha −1 mm −1 compared to 4 kg ha −1 mm −1 under dryland conditions (Musick et al, 1994).…”
Section: Crop Growth and Yieldsmentioning
confidence: 90%